PENGARUH BAHAN AJAR MOBILE WEB DALAM PEMBELAJARAN DISCOVERY TERHADAP PENCAPAIAN KOMPETENSI PESERTA DIDIK KELAS XI SMAN 4 PADANG PADA MATERI HUKUM NEWTON TENTANG GRAVITASI, USAHA, DAN ENERGI - Muhammad Rahfiqa Zainal; Djusmaini Djamas; Yohandri Yohandri (Universitas Negeri Padang, 2017)
The development of internet based teaching materials has been following as well as the progress of technology, as supporter of Curriculum 2013. The impact of technological developments makes students tend to use technology itself rather than textbooks. Low competences of students are caused by lack of interest and motivation in learning. Mobile web Internet-based is of teaching materials an alternative solution to increase the frequency of learning. Mobile web applied in teaching discoverylearning model. Discovery learning requires students to be active in seeking information on mobile web teaching materials.The aim of research was to investigate whether there is a meaningful impact on the mobile web in the teaching material to the achievement of discovery learning knowledge competence of students in class XI MIA 7 SMAN 4 Padang as well as its contribution to the knowledge aspect. The type of research used was quasi experiment with the design of randomized control group design and taking the sample using random cluster sampling techniqueis used in this research. The research instrument used for affective was observation sheet; for cognitive, it used multiple choice questions; for psychomotor, it used the skills assessment sheets and exercise assessment sheets on teaching materials mobile web. The results showed there were differences in average were the error rate used zero point zero five for both classes of samples for knowledge competencies while attitude and psychomotor have average differences. Large contributions of teaching materials mobile web on the competence of cognitive was 32.1%. The average value of the result of the attainment of physics on control class before and after using discovery learning also showed the different average which was the error rate used zero point zero five